Genotype-by-environment interaction and stability parameters for some new maize (Zea Mays L.) hybrids - Halbiza, A. A.; Balbaa, Maha G. (2010)
Three new white maize single-crosses, Nub104, 105 and 106, and seven new yellow maize single-crosses, Nub201 to Nub207, were developed during maize breeding program at Nubaria Agriculture Research Station during 2008 season. These hybrids along with two commercial hybrids, SC10 (white) and SC166 (yellow) were evaluated at five different environmental conditions in 2009 season. Results showed that differences among environments were significant (P < 0.01) and accounted for 42.5% of total variation for grain yield, 5.6% for number of days to mid-silking, 39.9% for plant height, 43.7% for ear position and 12.7% for late wilt resistance. Significant differences among hybrids were detected (P < 0.01) and accounted for 23.1 % of total variation for grain yield, 77.4% for number of days to mid-silking, 28% for plant height, 8.5% for ear position and 17.7% for late wilt resistance. Significant differences were observed for environment x hybrid interactions (P < 0.01) and accounted for 14.5% of total variation for grain yield, 5.5% for number of days to mid-silking, 13.9% for plant height, 13.3% for ear position and 22.1% for late wilt resistance. Regarding to (bi), Nub106, Nub203, Nub205, Nub206 and Nub207 were more stable hybrids. According to (S2y.x), Nub201, Nub202, Nub203, Nub204, Nub205 and Nub206 were more stable hybrids. For the 01 of each hybrid, Nub201, Nub202, Nub203 and Nub20S were the most stable hybrids. According to YS, Nub106 and Nub204 hybrids were identified as the most stable hybrids with high-yield, while Nub207 had high yield although it was unstable hybrid. Nub106 hybrid was significantly earlier than SClO, while, Nub204 and Nub207 hybrids were significantly earlier than the check hybrid 5C166. According to these results, Nub106, Nub204 and Nub207 hybrids were adapted to widely environments. Significant correlation was found between Sakha and each of Gemmiza and Mallawy. Also, highest correlation was observed between Gemmiza and Mallawy. Significant relationships were detected between 52y,x and both OJ (positive) and r2 (negative). Also, significant correlation was observed between OJ and r2. The importance of GE interactions and yield-stability analysis and regression analysis in determining adaptability of genotypes to a specific location or several locations was clearly reflected in this study. These results reflected that Nub106, Nub204 and Nub207 hybrids were adapted to widely different environments.
Includes reference.
Summary in Arabic.
1
Keywords: Corn -- Genetics; Corn -- Varieties; Corn -- Hybirds; Corn -- Yields; Genotype-environment interaction; Zea mays